1978
DOI: 10.1139/v78-194
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of prodiginines. 13C resonance assignments and enrichment patterns in nonyl-, cyclononyl-, methylcyclodecyl-, and butylcycloheptylprodiginine produced by actinomycete cultures supplemented with 13C-labeled acetate and 15N-labeled nitrate

Abstract: . Can. J Chem. 56, 11 55 (1978). Resonances in the 13C nmr spectra of nonylprodiginine, cyclononylprodiginine, methylcyclodecylprodiginine, and butylcycloheptylprodiginine were assigned using information from the literature, from high resolution spectra and double irradiation experiments, and from ' 3 C -1 5 N~~~p l i n g~ observed in samples of nonylprodiginine enriched with I5N. Supplementation of cultures with sodium [I-13C]-and [1,2-13C]acetate gave I3C-enriched prodiginines and the labeling patterns were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 5 publications
(7 reference statements)
1
26
0
1
Order By: Relevance
“…The red extract was subjected to column chromatography on a silica gel (60-120 mesh; Merck) column eluted with MeOH in CHCl 3 . Fractions eluted with 0.1 MeOH in CHCl 3 were found to be pure red fractions and had an absorbance maximum at 540 nm in acidic CHCl 3 , confirming published values for known prodigiosin analogs purified from Actinomycetes (Gerber et al 1978;Gerber 1975;Liu et al 2005;Tsao et al 2005). Thus combined and evaporated to yield PLPs (40 g L -1 ) as major ingredients of the producing fusant NRCF69.…”
Section: Extraction Purification and Estimation Of Plpssupporting
confidence: 76%
See 1 more Smart Citation
“…The red extract was subjected to column chromatography on a silica gel (60-120 mesh; Merck) column eluted with MeOH in CHCl 3 . Fractions eluted with 0.1 MeOH in CHCl 3 were found to be pure red fractions and had an absorbance maximum at 540 nm in acidic CHCl 3 , confirming published values for known prodigiosin analogs purified from Actinomycetes (Gerber et al 1978;Gerber 1975;Liu et al 2005;Tsao et al 2005). Thus combined and evaporated to yield PLPs (40 g L -1 ) as major ingredients of the producing fusant NRCF69.…”
Section: Extraction Purification and Estimation Of Plpssupporting
confidence: 76%
“…BA18591 and Streptomyces griseoviridis respectively, can also be considered as members of the prodigiosin family (Gerber et al 1978;Hayakawa et al 1992;Kojiri et al 1993). Although as with many secondary metabolites, the true physiological and ecological functions of PLPs in the producer organisms remains unclear; these tripyrrole molecules have received renewed attention owing to reported immunosuppressive, anticancer antifungal, antibacterial, antiprotozoal, antimalarial and trypanolytic activities (Demain 1995;Pérez-Tomás et al 2003;Zhang et al 2005).…”
mentioning
confidence: 99%
“…84 One such member of this family was extracted from the pigment of several Streptomyces species in 1975 by the Gerber group using chromatographic techniques, and initially assigned the structure 39 ( Figure 12) using mass spectral, UV-vis, and NMR analysis. 85 A revision of this structure to 40 (Figure 12) came three years later by the same author, 86 though confusion surrounding the correct structure and atropisomeric potential of the natural product remained, 87,88 until relatively recent studies put any ambiguities to rest and confirmed the correct general structure as 40. 89,90 It was in a study by Challis et al in 2010 that NOESY correlations of the HCl salts of extracted streptorubin B allowed for assignment of the major naturally occurring product as being the anticonfiguration with regards to the positioning of the C7ʹ n-butyl group relative to rings A and B, with the syn configuration only present in minor amounts.…”
Section: Streptorubin B: a Recently Synthesized Antibiotic From Red Pmentioning
confidence: 99%
“…Fr. C (97.7 mg) was subjected to successive silica gel column chromatograpies eluted with n-hexane/EtOAc gradients to yield cyclononylprodigiosin 10,12 (2,33.0 mg). Fr.…”
Section: Growth Extraction and Isolationmentioning
confidence: 99%
“…Fr. F (15.0 mg) was further purified by HPLC using a semipreparative C 18 column with an isocratic mobile phase of CH 3 CN:H 2 O (9:1) to give nonylprodigiosin 10,12 (3,4.0 mg, t R 10.8 min). …”
Section: Growth Extraction and Isolationmentioning
confidence: 99%